Optic fenestration in benign intracranial hypertension: case report - Munjal, Manish; Singla, Monika; Goel, Sahil; Rishi, Porshia; Tuli, Nitika; Sidhu, Harjinder; Munjal, Shubham (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Condition of raised intracranial pressure without any mass lesion and normal cerebrospinal fluid composition is termed as idiopathic intracranial hypertension or pseudotumor cerebri. Raised intracranial tension with visual effects was treated by trans-sphenoidal optic fenestration as an emergency intervention to salvage the vision. The lamina papyracea on either side was lifted off the orbital periosteum and thick bone of the ethmoid sphenoidal junction was drilled with a diamond burr to thin it and elevate the bone covering the optic nerve.